Severe muscle depletion predicts postoperative length of stay but is not associated with survival after liver transplantation. Issue 6 (26th March 2014) - Montano‐Loza, Aldo J.; Meza‐Junco, Judith; Baracos, Vickie E.; Prado, Carla M. M.; Ma, Mang; Meeberg, Glenda; Beaumont, Crystal; Tandon, Puneeta; Esfandiari, Nina; Sawyer, Michael B.; Kneteman, Norman
<x xml:space="preserve">Abstract</x> Muscle depletion or sarcopenia is associated with increased mortality in patients with cirrhosis; how it affects mortality after liver transplantation requires further study. In this study, we aimed to establish whether sarcopenia predicts increased morbidity or mortality after liver transplantation. We analyzed 248 patients with cirrhosis who had a computed tomography (CT) scan including the third lumbar vertebra before liver transplantation. Data were recovered from medical charts, the skeletal muscle cross‐sectional area was measured with CT, and sarcopenia was defined with previously published sex‐ and body mass index–specific cutoffs. One hundred sixty‐nine patients (68%) were male, and the mean age at transplantation was 55 ± 1 years. The etiologies of cirrhosis were hepatitis C virus (51%), alcohol (19%), autoimmune liver diseases (15%), hepatitis B virus (8%), and other etiologies (7%). Sarcopenia was present in 112 patients (45%), and it was more frequent in males (P = 0.002), patients with ascites (P = 0.02), and patients with higher bilirubin levels (P = 0.05), creatinine levels (P = 0.02), international normalized ratios (P = 0.04), Child‐Pugh scores (P = 0.002), and Model for End‐Stage Liver Disease scores (P = 0.002). The median survival period after liver transplantation was 117 ± 17 months for sarcopenic patients and 146 ± 20 months for nonsarcopenic patients (P = 0.4). Sarcopenic patients had longer hospital stays (40 ± 4 versus 25 ± 3 days; P = 0.005) and a higher frequency of bacterial infections within the first 90 days after liver transplantation (26% versus 15%, P = 0.04) in comparison with nonsarcopenic patients. In conclusion, sarcopenia is one of the most common complications in patients with cirrhosis and is predictive of longer hospital stays and a higher risk of perioperative bacterial infections after liver transplantation, but it is not associated with increased mortality. Liver Transpl 20:640–648, 2014. © 2014 AASLD.